The disappearance of Eleanor Rigby - Benson, Ned, 1977-; McAvoy, James, 1979-; Chastain, Jessica, 1977-; Hader, Bill, 1978-; Weinstein Company Home Entertainment (Firm); Anchor Bay Entertainment, Inc. ([Place of publication not identified] : [Publisher not identified], 2015)
Once happily married, Connor and Eleanor suddenly find themselves as strangers longing to understand each other in the wake of tragedy. The film explores the couple's story as they try to reclaim the life and love they once knew and pick up the pieces of a past that may be too far gone.
Original production: c2014.
James McAvoy, Jessica Chastain, Bill Hader, Viola Davis, Ciarán Hinds.
Rating: R; for language.
DVD, region 1, anamorphic widescreen presentation (2.40:1); Dolby digital 5.1.
English dialogue; Spanish subtitles; English subtitled for the deaf and hard of hearing.
Keywords: Married people -- Drama -- Videodiscs; Man-woman relationships -- Drama -- Videodiscs; Films for the hearing impaired; Feature films; Romance films